Initiating Electric Vehicle Price Index and its Economic Factors: Evidence from the Stock Exchange of Thailand - Aleenajitpong, Natdanai; Kaewpunpong, Karn (International Journal of Energy Economics and Policy, 2026)
The research aimed to develop a price index for electric vehicle companies listed on the Stock Exchange of Thailand and to examine the influence of macroeconomic factors on the Electric Vehicle Industry Index. The analysis employed both descriptive and inferential statistics, utilizing a multiple regression approach based on the least squares method. The study served as an example for constructing an index within the Thai stock market and provided insights into how macroeconomic factors influence the Electric Vehicle Industry Index. The findings indicated several factors affecting the stock price index of the electric vehicle industry. Notably, the exchange rate between the US dollar and the Thai baht, as well as the price of Dubai crude oil, showed a statistically significant inverse relationship with the electric vehicle index. Additionally, the total return index of the stock exchange of Thailand exhibited a statistically significant positive correlation with the electric vehicle index, while the consumer price index did not demonstrate any significant relationship with it. The results can assist investors and stakeholders in investment decisions in electric vehicle manufacturers by identifying key factors impacting the EV index and assessing the effects of macroeconomic conditions on their performance.